Transoral removal of a hilo‐parenchymal submandibular sialolith. Issue 5 (27th May 2022) - Kataoka, Yo‐Hei; Kojima, Yoshihiro; Ishibashi, Ruri; Nakao, Yuji; Yamamura, Koji; Takahashi, Shotaro; Hashiba, Takafumi; Matsue, Takahito
Abstract: In sialolithiasis, the lithiasis is often large and located at the junction of the middle and posterior third of the duct, in the hilum region. In such cases, transoral approach for submandibular lithiases (TASL) is a useful treatment of choice in patients with large submandibular stones that can be palpated bimanually. Abstract : TASL is an established minimally invasive technique described more than 20 years ago. However, it is important to report these findings in literature, since previous reports suggested that it is an underutilized surgical technique.